Facebook API Developers Guide - Graham, Wayne (Apress, 2012)
Facebook (http://www.facebook.com) has grown phenomenally over the past several years from an Ivy League social web application to the second largest social web site on the Internet. The creators of Facebook have done an impressive job focusing their social software on the college demographic. In a natural progression of the social network, Facebook recently extended its network by developing a platform for developers to create new applications to allow Facebook users to interact in new and exciting ways.